an An analysis of irony in “harrison bergeron” by kurt vonnegut.jr - rahayu oktarini (STKIP PGRI Lubuklinggau, 2020)
This paper concerns the analysis of Irony in Harrison Bergeron by Kurt Vonnegut.JR. Kurt vonnegut.JR is an American writer, in that story he is willing to surprise the reader by providing many scenes of oppression carried out through equality and he likes to use ironic pictures to insinuate his criticisms. According to Gibbs (2008) in The Cambridge Handbook of Metaphor and Thought, “irony emphasize the difference between two states of affairs, making plain which is true” (p.458). Overall the story, many of the sentences and events have meaning that he strongly opposes the government which adheres to a system of equality or egalitarianism. Descriptive qualitative research method was used in conducting the research. The technique of qualitative method are used to find and indetify the data. The types of irony that found in this research are verbal irony and situational irony. This paper intends to analyze the story from the angle of the use of irony in the story, to get clear description of the types of irony find in this story and implied the meaning of each irony in Kurt Vonnegut’s story “Harrison Bergeron”.